In Vitro Biocompatibility of Diazirine‐Grafted Biomaterials. Issue 21 (22nd September 2020) - Djordjevic, Ivan; Wicaksono, Gautama; Solic, Ivan; Steele, Terry W. J.
Abstract: Photoactivation of aryl‐diazirines is an emerging method of rapid, covalent crosslinking under ambient conditions. These attributes make those compounds candidates for grafting onto inert polymer backbones in order to produce stimuli‐sensitive biomaterials. However, no risk assessments are available to gauge the toxicity of the leachable components after crosslinking activation. Herein, a stimuli‐sensitive biomaterial is formulated from diazirine‐grafted polycaprolactone tetrol. Also known as CaproGlu, this biomaterial undergoes UVA‐activated crosslinking, with many positive attributes toward bioadhesive applications; hydrophobic, solvent‐free, liquid at room temperature, and transitions into a foam biorubber after mild UVA illumination. As a model diazirine‐grafted biomaterial, hydrolyzed CaproGlu leachates are evaluated for genotoxicity and skin sensitization, namely, Ames test, direct peptide reactivity, and ARE‐Nrf2 luciferase assays. The degradation products of diazirine‐mediated crosslinking observe little to no risk of in vitro genotoxicity or skin sensitization. Abstract : Aryl‐diazirines are an emerging strategy to induce rapid covalent crosslinking and polymerization under ambient conditions upon light and voltage activation. Aryl‐diazirine‐grafted polyester, CaproGlu, rapidly undergoes liquid‐to‐elastomer transition with low‐energy UVA activation. Hydrolyzed leachates from CaproGlu are assessed for genotoxic and sensitization risks with respect to UVA dose and degree of hydrolysis. Biocompatibility results compare favorably to the nontoxic, polycaprolactone tetrol.